Analysis of Service Quality in m-Health - Annisa Nuria Rodhiani, Rahmat Nurcahyo, Muhammad Dachyar (International Journal of Advanced Science and Technology, 2020)
The rapid development of technology has impacted on several fields including digitalrevolution of health sector. In Indonesia, the journey to ease is becoming more open, nowthat distance treatment is increasingly possible, people are starting to use their electronicdevices to consult with doctors, order and buy medicines, and even to collect patienthealth data. Although mobile health creates positive change, concerns about quality havean impact on users’ satisfaction, continuing intentions, and quality of life. Thus, theimpact of perceived quality of this service becomes an important dimension indetermining the success or failure of the mobile health platform. The main purpose of thisstudy is to determine attribute that affect customer satisfaction using Kano model andSERVQUAL which better defines customer expectations and measures the effects of theseattributes in determining the success or failure of mobile health platform.